Who are you, really? : the surprising puzzle of personality - Little, Brian R. (New York: TED books, 2017)
"Traditionally, scientists have emphasized what they call the first and second natures of personality--genes and culture, respectively. But today the field of personality science has moved well beyond the nature vs. nurture debate. In Who Are You, Really? Dr. Brian Little presents a distinctive view of how personality shapes our lives--and why this matters. Little makes the case for a third nature to the human condition--the pursuit of personal projects, idealistic dreams, and creative ventures that shape both people's lives and their personalities. Little uncovers what personality science has been discovering about the role of personal projects, revealing how this new concept can help people better understand themselves and shape their lives" -- provided by publisher.
Scanning your personality: the big picture -- Personal projects: the doings of personality -- Personal contexts: the social ecology of project pursuit -- The myth of authenticity: the challenge of being oneself -- Well-doing: the sustainable pursuit of core projects.
Includes bibliographical references (pages 98-105).
Keywords: Personality; Self-perception.; Mental health; Emotions; Change (Psychology); BODY, MIND & SPIRIT / Inspiration & Personal Growth; PSYCHOLOGY / Emotions; PSYCHOLOGY / Personality; Change (Psychology); Emotions; Mental health; Personality; Self-perception.; Nonfiction; Self-help publications; Self-help publications